OGC P11 Recurrent laryngeal nerve injury after oesophagectomy: incidence, management and clinical sequelae. (7th December 2022) - Chien, Siobhan; Gall, Lewis; Khan, Khurram; Craig, Carol; MacKay, Colin; Macdonald, Andrew; Forshaw, Matthew
Abstract: Background: Recurrent laryngeal nerve palsy (RLNP) resulting from injury during the cervical-stage of oesophagectomy is a recognised complication that can be associated with significant morbidity. This study aimed to investigate the incidence of RLNP within our local practice, to describe its management, short- and long-term sequelae. Methods: Consecutive patients undergoing transhiatal oesophagectomy or 3-stage oesophagectomy with cervical anastomosis for both benign and malignant disease within a single UK regional centre between 1 January 2010 and 31 December 2019 were included from a prospectively collected database. Electronic records were interrogated and patients dichotomised into two groups – postoperative RLNP (paresis or paralysis) compared to no RLNP. Results: 182 patients were eligible for analysis. 33 patients (18.1%) developed RLNP after oesophagectomy. Patients with RLNP were significantly more likely to develop postoperative pneumonia (57.6% vs. 34.2%; p=0.017) and ARDS (9.1% vs. 0.7%; p=0.019), and were more likely to require ICU admission (30.3% vs. 14.8%; p=0.044). They were also found to have a longer length of hospital stay (24 vs. 15 days; p=0.001). 18 patients (54.5%) with RLNP required ENT review with 3 patients (9.1%) requiring vocal cord collagen injection. After a median 34 months (IQR 21.75-67) follow-up, 36.4% (12/33) patients had made a full and 42.4% (14/33) patients had made a partial recovery. Conclusions: Judicious surgical technique in an attempt to avoid initial RLN injury, as well as proactive involvement of SALT and ENT specialists when injury does occur, are vital to reduce the significant pulmonary morbidity associated with this common complication of oesophagectomy.